The interaction of evodiamine and rutaecarpine with DPPC liposomes. (May 2022) - Gu, Jia-Yu; Cao, Bo-Bo; Hao, Xiao-Lei; Yu, Dan-dan; Wu, Rui-Guang
Highlights: DSC, synchrotron XRD and FTIR techniques have been employed in this study. EVO and RUT affect liposome membrane in a concentration-dependent manner. The effect of RUT on liposome membrane was stronger than that of EVO. Abstract: Evodiamine and rutaecarpine, derived from the traditional chinese medicine Euodia rutaecarpa (Juss.) Benth, have many similar pharmacological effects, but their pharmacological mechanisms are not exactly the same. In this study, liposomes were used as the model of biomembrane. DSC, synchrotron XRD and FTIR techniques have been employed to investigate and compare the interaction of evodiamine and rutaecarpine with DPPC liposomes. The results show that evodiamine and rutaecarpine remarkably affect the DPPC in a concentration-dependent manner. But the concentration dependence of the two drugs is obviously different. The effect of rutaecarpine on liposome membrane was stronger than that of evodiamine, which might be related to the different pharmacological mechanism of evodiamine and rutaecarpine. This study will play an important role in the further investigation of interaction of drugs with biomimetic membranes and further investigation of pharmacological mechanisms of drugs.